Change in Financial Firms and Avoiding Harm to People and Environment - Holland, John (Frontiers in Sustainability, 2022)
This paper explores issues of Corporate Social Responsibility (CSR) and Net Zero change in financial firms, with reference to top teams, employees, customers, citizens, and other stakeholders. It proposes a holistic approach to managing these problems of change, of reducing harm to people and environment, and contributing to social sustainability. Changes in financial firms and financial markets to become CSR and Net Zero oriented are being driven by major external change. There are increased demands to reduce harm to individuals, teams, and the environment, and to maintain social sustainability. The change pressures combine with problematic internal firm and external network predispositions. These exacerbate barriers to change and contribute to CSR and Net Zero problems. The paper uses a conceptual framework or ‘Behavioural theory of the financial firm’ (BTTF) to think holistically about these problems and their impact on humans, their social systems, and physical systems. The BTFF is a basis for management and stakeholders to promote change based on credible organizational practices and prevention of exploitation of human capital and social conditions. These support social sustainability and occupational health and safety, or the ability of current and future generations to create healthy, living, and liveable communities in financial firms, and amongst external stakeholders. This holistic narrative and metaphor approach is a means for individuals and teams in the firm and externally to answer the question, ‘What is going on here?’ when responding to uncertainty (p10, p528, Kay and King, 2020).This approach has potential ‘to make a difference’ in; researching, learning, thinking, and believing about desirable actions and responses to problems and harms, and to demands for Net Zero and CSR oriented change in financial firms and wider systems (Shiller, 2019).